History in the Early Years. - Cooper, Hilary (Taylor and Francis, 2013)
History in the Early Years is an innovative and accessible guide to helping young children explore the past through their environment, family history and story. This fully revised edition includes guidance on introducing children to the past at the Foundation Stage in school and pre-school settings. Throughout it shows how the requirements of the early years curriculum can be met in innovative ways, and is fully illustrated by case study examples of children's learning and also supported by recent research. The book will support both new and experienced early years practitioners in.